2018
DOI: 10.3329/bjsr.v30i1-2.36115
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum system of Srikail gas field using sequence stratigraphy

Abstract: A sequence stratigraphic analysis was carried out on the sedimentary packages of parts of the Bengal Basin hydrocarbon province. This paper focuses on the identification of petroleum system of Srikail Gas Field within eastern folded belt of Bengal basin using sequence stratigraphic concept. Three strike and five dip seismic lines are used in this work and data analysis is done using Petrel 2015 software. Seismic line-2 (SK-2) of Srikail is good in resolution and is used here only for identifying potential petr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…9). These results are congruent with previous studies that found the association between sequence deposition and fluctuation of sea level (Najman et al 2012;Hossain et al 2018).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…9). These results are congruent with previous studies that found the association between sequence deposition and fluctuation of sea level (Najman et al 2012;Hossain et al 2018).…”
Section: Resultssupporting
confidence: 93%
“…On the contrary, the less intense channel cutting and lesser width imply the evidence of relatively higher sea level position during the rest of the sequence deposition. This finding is aligned with the previous study conducted by Najman et al (2012) and Hossain et al (2018) indicating similar characteristics of seismic mega sequence-2. The sequence remnants act as reservoir rocks preserved between multiple, down-cutting channels.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation